IMPROVING CHAIN STITCH STABILITY: A COMPREHENSIVE REVIEW OF FAULTS AND TECHNIQUES TASHKENT INSTITUTE OF TEXTILE AND LIGHT INDUSTRY - Palvannazirova Nasiba; Butovskiy P. M.; Agzamov M. M. (American Journals Publishing, 2024)
This article explores the impact of low-quality needles, thread, and machine parts wear on chain-stitch defects, as well as the resulting effects on the stitch's structure and strength properties. Various technological and organizational measures are proposed to enhance the stability of the chain stitch formation process.
Keywords: Chain stitch, stitch defects, sewing equipment wear, needle quality, process optimization